Karakteristik pasien ocular surface squamous neoplasia di Pusat Mata Nasional RS Mata Cicendo periode Januari 2012- Juni 2014 - Sandraningrum Sandraningrum; M Rinaldy Dahlan (Majalah Oftalmologi Indonesia, 2017)
Background: Ocular surface squamous neoplasia (OSSN) is a broad term encompassing conjunctival intraepithelial neoplastic lesions (CIN) and invasive squamous cell carcinoma (SCC) of conjunctiva and cornea. The purpose of this study is to describe the demographic, clinical, therapy and histopathology characteristics of OSSNs patients in Cicendo Eye Center within period of January 2012 â€“ June 2014. Methods: Patient medical records were reviewed. Fourty patients of biopsy-proven OSSN at Cicendo Eye Centre from January 2012 until June 2014 were reviewed. Results: Data was collected from 40 patients (41 eyes), OSSN was more frequent in men (62.5%) and had unilateral presentation (97.5%). The mean patient age was 45.9Â±14.7 years. The most common complaint was lump on the ocular surface (50%). The size of lesion was mostly less than 2 mm (62.5%). All of the patients were managed with surgery using wide excision and histopathology examination, of whom 46.4% cases were managed with wide excision only, 41.4% cases were managed with wide excision and application of topical mitomycin C (MMC), 12.2% cases were managed with wide excision, application of topical MMC, and cryotherapy. Histopathology examination revealed that 41.5% cases were CIN, 19.5% cases were carcinoma in situ, and 39% cases were invasive SCC. Conclusions: Patients with OSSN who came to Cicendo Eye Center were mostly male and had unilateral presentation. The most common clinical sign and symptom were ocular surface mass with size of the lesion less than 2 mm. Management of patient with OSSN is mostly excisional surgery only. Majority of histopathology examination showed CIN.